2019
DOI: 10.1002/wfp2.12011
|View full text |Cite
|
Sign up to set email alerts
|

Managing subjective well‐being of organic food consumers through sustainability orientation, environmental consciousness, and skepticism in Thailand: Mediating role of organic food consumption

Abstract: Subjective well-being of consumers is turned out to be a modern and the most important issue for green marketers.World's food policy which is mostly revolving around consumption of organic food is also making well-being a center piece of all its discussions. This study has contributed by checking the impact of consumer sustainability orientation (CSO), skepticism and environmentally conscious purchase behavior (ECPB) on subjective well-being of consumers in mediating role of organic food consumption. A quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Consequently, low awareness among consumers limits their ability to differentiate between organic and non‐organic food (Tandon et al, 2020b), leading to skepticism towards them (Sadiq et al, 2021a). As a result, prior studies (Hwang, 2016; Siriattakul et al, 2019) have demonstrated that consumers are often skeptical about adopting organic foods. It is, therefore, trust that reduces consumers' skepticism and influences their attitudes and behaviors toward organic food (Tandon et al, 2020a).…”
Section: Hypotheses and Research Model Developmentmentioning
confidence: 99%
“…Consequently, low awareness among consumers limits their ability to differentiate between organic and non‐organic food (Tandon et al, 2020b), leading to skepticism towards them (Sadiq et al, 2021a). As a result, prior studies (Hwang, 2016; Siriattakul et al, 2019) have demonstrated that consumers are often skeptical about adopting organic foods. It is, therefore, trust that reduces consumers' skepticism and influences their attitudes and behaviors toward organic food (Tandon et al, 2020a).…”
Section: Hypotheses and Research Model Developmentmentioning
confidence: 99%
“…The consumers' sense of environmental duty and their personal preferences are driving this trend toward sustainable consumption (Jermsittiparsert et al, 2019). Environmental consciousness has a significant impact on organic food consumption (Siriattakul et al, 2019), and several studies have found that environmental consciousness significantly influences consumers' purchasing attitude toward organic food products (Farhan, 2020;Wang et al, 2020). The following hypotheses were therefore formulated:…”
Section: The Role Of Perceived Consciousness On Customers' Consumptio...mentioning
confidence: 99%